Code Index Modulation and Spatial Modulation: A New High Rate and Energy Efficient Scheme for MIMO systems - Cogen, Fatih; Aydin, Erdogan; Kabaoglu, Nihat; Basar, Ertugrul; Ilhan, Haci (IEEE, 2018)
In this paper, in order to increase data rate, error performance and energy efficiency in wireless communication systems, a new multiple-input multiple-output (MIMO) transmis sion scheme, called code index modulation and spatial modulation (CIM-SM), is proposed over the Nakagami-m fading channel by combining recently two promising modulation techniques, SM and CIM. In the CIM-SM scheme, incoming data bits specify activated transmit antenna indices, two modulated symbols as well as their corresponding spreading code indices. Therefore, the information bits are conveyed not only by the two modulated symbols but also by the active antenna indices of SM as well as the spreading code indices. Consequently, the proposed CIM-SM scheme spends less transmission power while performing faster data transmission compared with the conventional direct sequence spread spectrum (DS-SS), SM and CIM-SS systems. Our computer simulations show that CIM-SM scheme provides considerably better error performance than DS-SS, SM and CIM-SS systems. In addition, the performance analysis of the proposed system is performed over the Nakagami-m fading channels for BPSK modulation.
Keywords: Spatial modulation; code index modulation; MIMO systems and direct sequance spread spectrum; Engineering; Telecommunications